1995
DOI: 10.2166/wst.1995.0462
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater treatment by stabilization pond: Marrakesh experiment

Abstract: This paper presents results of two years of investigations on three types of wastewater stabilization pond treatment systems, purifying a raw urban wastewater, in the arid climate of Marrakesh. The systems tested were: two lined water hyacinth ponds, two lined facultative ponds and one anaerobic pond. During the course of the experiment, organic load, nutrients and parasitical load were studied. Results show that the macrophytic ponds were more efficient to reduce organic load (90% of TSS and 78% of COD) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
1
6
0
3
Order By: Relevance
“…From Figure 3, it can be observed that, only in two situations (6.7%), fecal coliform counts were in agreement with category A of the WHO guidelines (1989). Similar results on coliform counts were observed in studies carried out worldwide ( Devaux et al, 2001 ; Madera et al, 2002 ; Oron et al, 2001 ; Ouazzani et al, 1995 ). In Brazil, no microbiological and physicochemical standards for wastewater reuse in agricultural irrigation have been established.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…From Figure 3, it can be observed that, only in two situations (6.7%), fecal coliform counts were in agreement with category A of the WHO guidelines (1989). Similar results on coliform counts were observed in studies carried out worldwide ( Devaux et al, 2001 ; Madera et al, 2002 ; Oron et al, 2001 ; Ouazzani et al, 1995 ). In Brazil, no microbiological and physicochemical standards for wastewater reuse in agricultural irrigation have been established.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were observed by Amahmid et al (2002) and Semenas et al (1999) . Cutolo et al (2006) emphasized that the presence of these organisms is the main problem in wastewater reuse, although other researchers reported total elimination of helminth eggs from treated wastewater with the use of stabilization pond systems ( Ceballos et al, 1995 ; Madera et al, 2002 ; Marecos do Monte et al, 1996 ; Ouazzani et al, 1995 ). In general, effluents carry a massive egg load.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is a region with hot climate where conditions for the treatment of wastewater by stabilization ponds are very favorable. Waste stabilization ponds are a simple, low-cost and low-maintenance extensive process for treating wastewater, and well adapted to low socio-economic conditions in developing countries [23,24]. A typical system consists of several constructed ponds operating in series.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos realizados por pesquisadores mostraram que os efluentes de sistemas de lagoas de estabilização são adequados para irrigação restrita, que inclui sua utilização em culturas de cereais, forragem, pastos e culturas arbóreas (OUAZZANI et al, 1995). Outros estudos indicaram a utilização de efluentes de sistemas de lagoas para irrigação irrestrita, desde que submetidos a tratamento final em lagoas de maturação ou armazenamento do efluente em reservatórios para tratamento, nos quais os patógenos são eliminados (MARA, 1996;MARA et al, 1996;PEARSON et al, 1996a, MARA e PEARSON, 1999.…”
Section: As Lagoas De Estabilizaçãounclassified
“…Por outro lado, processos adicionais estão disponíveis para melhorar a qualidade dos efluentes, dentre as quais estão os filtros de pedra, a filtração intermitente em leito de areia, a aplicação no solo para irrigação de culturas ou sistemas alagados (wetlands). Ouazzani et al (1995) compararam a eficiência de remoção de matéria orgânica, nutrientes e parasitas em três tipos de lagoas, lagoa macrofítica, lagoa facultativa e lagoa anaeróbia alimentadas com esgoto sanitário. Os resultados mostraram que a utilização de macrófitas na lagoa gerou uma melhor eficiência de redução de matéria orgânica (90% de redução de sólidos suspensos totais -SST -e 78% de redução nos valores de DQO) em comparação com a lagoa facultativa (37% para SST e 50% para DQO).…”
Section: Tipos E Desempenho De Lagoas De Estabilização -Consideraçõesunclassified